2009
DOI: 10.1002/bio.1126
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence from luminol solution after illumination of a 355 nm pulse laser

Abstract: Chemiluminescence (CL) on the time scale of microseconds to milliseconds from luminol solution after illumination of a 355 nm pulse laser is reported. It was found that the CL is the emission from 3-aminophthalate ion (AP*). In CL decay after the pulse laser illumination, a peak was observed from about 200 to 30 micros depending on the laser power and the luminol concentration. It seemed that there was a fast and slow decay process; their kinetics were greatly dependent on the laser power and the luminol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…On the other hand, CL spectra of the both CL systems were basically the same as that from a typical luminol CL such as luminol–H 2 O 2 –K 4 Fe(CN) 6 system, with a maximum CL wavelength of about 430 nm. [18] This suggested that the emitters were AP* in both CL systems. Qualitatively, no remarkable difference was observed between the two CL systems in absorbance, fluorescence and CL spectra.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, CL spectra of the both CL systems were basically the same as that from a typical luminol CL such as luminol–H 2 O 2 –K 4 Fe(CN) 6 system, with a maximum CL wavelength of about 430 nm. [18] This suggested that the emitters were AP* in both CL systems. Qualitatively, no remarkable difference was observed between the two CL systems in absorbance, fluorescence and CL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper, it was discussed that there seemed to be an exponential function during 0.15–1.00 mJ/pulse, a linear function during 1.00–2.55 mJ/pulse and another exponential function during 2.55–3.20 mJ/pulse between the 355 nm pulse laser‐induced CL intensity and the laser power. [18] Here, the relation between the 355 nm pulse laser‐induced luminol CL intensity and laser power was further studied by using a log–log plot as shown in Fig. 2(B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations